2021
DOI: 10.3389/fevo.2021.765488
|View full text |Cite
|
Sign up to set email alerts
|

Reconnecting the Elwha River: Spatial Patterns of Fish Response to Dam Removal

Abstract: The removal of two large dams on the Elwha River was completed in 2014 with a goal of restoring anadromous salmonid populations. Using observations from ongoing field studies, we compiled a timeline of migratory fish passage upstream of each dam. We also used spatially continuous snorkeling surveys in consecutive years before (2007, 2008) and after (2018, 2019) dam removal during summer baseflow to assess changes in fish distribution and density over 65 km of the mainstem Elwha River. Before dam removal, anadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…https://wildlife.ca.gov/Fishing/Ocean/Regulations/Salmon#commercial ). A longer-term solution to increase survival may be reintroductions to formerly accessible habitat upstream of impassable dams ( Duda et al, 2021 ; FitzGerald et al, 2021 ), as these streams are generally cooler ( FitzGerald et al, 2021 ) and because spring-run have been disproportionately extirpated relative to fall-run due to the loss of this high-elevation habitat ( Beechie et al, 2006 ; Gustafson et al, 2007 ; McClure et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…https://wildlife.ca.gov/Fishing/Ocean/Regulations/Salmon#commercial ). A longer-term solution to increase survival may be reintroductions to formerly accessible habitat upstream of impassable dams ( Duda et al, 2021 ; FitzGerald et al, 2021 ), as these streams are generally cooler ( FitzGerald et al, 2021 ) and because spring-run have been disproportionately extirpated relative to fall-run due to the loss of this high-elevation habitat ( Beechie et al, 2006 ; Gustafson et al, 2007 ; McClure et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring methods included: 1) environmental DNA (eDNA), 2) ichthyoplankton (fish eggs) collection, 3) boat electrofishing, and 4) passive integrated transponder (PIT) telemetry, which together provide information on habitat use from the population to individual level. Given the rapid use of restored habitat observed in other rivers [ 12 , 13 , 15 ], we similarly predict that river herring will re-occupy restored habitat in the Patapsco River within three years of the removal of Bloede Dam.…”
Section: Introductionmentioning
confidence: 93%
“…Despite the construction of fish passage structures in dams, such as ladders and lifts, upstream passage efficiency remains at a low 20% for most anadromous species [ 9 ]. On the other hand, studies monitoring fish responses to dam removals have consistently observed that removing physical barriers restores longitudinal connectivity, allowing numerous migratory species to re-occupy upstream reaches [ 10 13 ]. A growing number of dam removal projects in North America have cited recovery of fish passage and ecological restoration as a primary goal [ 14 ], including Elwha Dam in Washington State, U.S. [ 13 ] and Edwards Dam in Maine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dam removal is increasingly being used as a tool for fisheries conservation and stream restoration. Removal of dams has been shown to benefit fish and other biota in both marine and freshwater ecosystems (Mattocks et al, 2007; Dias et al, 2019, Duda et al, 2021) as well as physical processes such as sediment and nutrient transport (Harrison et al, 2018, Warrick et al, 2019). Furthermore, removal of aging dams is beneficial where dam failure risk and safety hazards of the structure and associated infrastructure are of public concern.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits to fish populations are difficult to predict for many reasons including, the diversity of life cycles of migratory fishes, data limitations, model limitations, temporal and spatial changes to stream habitat following dam removal (e.g. Roni 2019; Duda et al, 2021), among many others. Although some work has been completed documenting fish and habitat response to dam removal, we contend there is no standard or widely applied approach for making quantitative predictions of the ecological benefits of dam removal.…”
Section: Introductionmentioning
confidence: 99%